mHealth program on diabetes mellitus management: a review - Firdaus, Mohd Khairul Zul Hasymi; Jittanoon, Piyanuch; Che Hasan, Muhammad Kamil (2019)
Background: People nowadays strongly hold on smartphone in their daily life activities as a result of technology advancement. Health care system should move forward to match industrial revolution. Technology integration should provide an insight for appropriate intervention in health care system i.e. engagement in required health behavior such as prevention for diabetic complications. Purpose: to explore existing mobile health intervention program for diabetic foot care. Methods: Relevant articles were retrieved via online database (CINAHL, ProQuest, Science Direct, BMJ). Diabetic foot care mobile application, diabetic care mobile application, mobile health program for diabetic, mobile apps for diabetic foot care are among keywords that being used in retrieving relevant articles. PICO analysis carried out after categorizing articles according to The Joanna Briggs Institute’s level of evidence. Findings: 2153 of articles were retrieved with only 10 eligible for data qualitative synthesis. Duration of articles selected is within 10 years (2008-2018). The articles were categorized as systematic review (n = 1), randomized control trials (n = 1), cohort study (n = 1), pre-test-post-test study (n = 3), cross-sectional (n = 2), bench research/expert opinion (n = 2). Different types of mobile health program, different target group of mobile health (either to professional or patient), and integration of face to face and long distance session to patients are among the findings extracted from the articles. Conclusions: Most of mobile health interventions carried out caters for general diabetes care with minimal component of foot care. No specific study on mobile application program focus on foot care.